Calculations of the thermal conductivities of ionic materials by simulation with polarizable interaction potentials. - Ohtori, N; Salanne, M; Madden, P (2009)
Expressions for the energy current of a system of charged, polarizable ions in periodic boundary conditions are developed in order to allow the thermal conductivity in such a system to be calculated by computer simulation using the Green-Kubo method. Dipole polarizable potentials for LiCl, NaCl, and KCl are obtained on a first-principles basis by "force matching" to the results of ab initio calculations on suitable condensed-phase ionic configurations. Simulation results for the thermal conductivity, and also other transport coefficients, for the melts are compared with experimental data and with results obtained with other interaction potentials. The agreement with experiment is almost quantitative, especially for NaCl and KCl, indicating that these methodologies, perhaps with more sophisticated forms for the potential, can be used to predict thermal conductivities for melts for which experimental determination is very difficult. It is demonstrated that the polarization effects have an important effect on the energy current and are crucial to a predictive scheme for the thermal conductivity.